Dance for Parkinson's—The effects on whole body co-ordination during turning around. (June 2017) - Hulbert, Sophia; Ashburn, Ann; Roberts, Lisa; Verheyden, Geert
Highlights: Ballroom and Latin American dance classes affect turning in Parkinson's. Dancers become more' en bloc' in their turning behaviour. Dancing enables better co-ordination between axial and perpendicular body segments. Multi-dimensional interventions (dance) require analysis by multiple turn variables. Abstract: Objective: To investigate the effects of ballroom and Latin American dancing classes on turning in people with Parkinson's. Design: This study employed a randomised, controlled, experimental design. Setting: Dance classes were performed in a community dance centre in Southern England and all assessments took place a gait laboratory. Participants: Twenty-seven people with mild-moderate Parkinson's participated. Intervention: Participants were randomly allocated to receive either 20, 1-h dancing classes over 10 weeks (n = 15), or a 'usual care' control group (n = 12). Main outcome measure: Twelve, 180° on-the-spot turns to the predicted/un-predicted and preferred/un-preferred direction were analysed for each participant, using 3-dimensional motion analysis before and after the intervention period, alongside clinical measures. Results: Movement of the head, pelvis, and feet during turning in people with Parkinson's are affected by dancing with tighter coupling of body segments. Significant 4-way interactions between the groups, over time and turn style, with longer latency of the head (p = 0.008) and greater rotation in the pelvis (p = 0.036), alongside a trend of slower movement of the first (p = 0.063) and second (p = 0.081) foot in controls were shown, with minimal change in dancers. All interactions were affected by the type of turn. No significant differences were found in the centre of mass displacement, turn time or clinical measures. Conclusion: Those who danced were better able to coordinate their axial and perpendicular segments and surprisingly became more 'en bloc' in their turning behaviour, suggesting this may be a beneficial adaptation, rather than a maladaptive result of Parkinson's, as previously suggested.